Retinopathy Of Prematurity: Leading Cause Of Childhood Blindness. Problems And Treatment - Chafloque-Cervantes, Augusto (2019)
Retinopathy of prematurity is the leading cause of childhood blindness in Peru and in many countries whose survival rate in newborns of very low birth weight has increased, this due to the largest biotech support in the management of intensive care neonatal. It is considered appropriate to review the aspects related to the pathophysiology, multifactorial etiology and epidemiology of this disease. Screening methods used with associated risk factors, the international classification in the diagnosis and current and experimental treatments based on multicenter studies with the respective recommendations are also emphasized. Finally pathological eye is exposed to increased risk of suffering those infants with a history of retinopathy of prematurity.